Photoinduced cytotoxicity of a photochromic diarylethene via caspase cascade activation1. Issue 54 (11th July 2015) - Okuda, Jun-ya; Tanaka, Yukimi; Kodama, Ryuhei; Sumaru, Kimio; Morishita, Kana; Kanamori, Toshiyuki; Yamazoe, Seiji; Hyodo, Kengo; Yamazaki, Shohei; Miyatake, Tomohiro; Yokojima, Satoshi; Nakamura, Sinichiro; et al.
<x xml:space="preserve">Abstract</x> The photo-generated closed-ring isomer of a diarylethene showed cytotoxicity to induce the apoptosis to the MDCK cells upon 436 nm light irradiation.